Ships and Maritime Activities in the North-eastern Indian Ocean: re-analysis of rock art of Tham Phrayanaga (Viking Cave), southern Thailand - Sukkham, Atthasit; Taçon, Paul S. C.; Tan, Noel Hidalgo; Muhamad, Asyaari Bin (The International journal of nautical archaeology, 2017)
Tham Phrayananga is a limestone cave on Phi Phi Le Island in the Andaman Sea, off south-west Thailand. A 2010 survey recorded 80 painted figures on the cave wall, in three different panels. They include nine identifiable ship types, other unidentified ships, non-marine images and a Jawi script. They are monochrome (black, red-brown, or dark-brown), or bichrome (dark-brown with yellow-brown, or red-brown with black). The vessels portrayed can be compared with local and overseas ships from China, Europe and Indonesia. Whether local or from distant ports, all were involved in the Southeast Asian maritime trade and voyages of the 15th-20th centuries. 东北印度洋的船舶与海洋活动༚泰国南部Tham Phrayanaga (维京洞穴) 岩石艺术的再分析 Tham Phrayananga是一个在泰国西南安曼海皮皮岛上的石灰岩洞穴。2010年的一-调查在三块不同的画板上记录了绘在岩壁上的80个图像。它们包括九种可识别的船只类型、其他无法辨别类型的船舶-非海相图像和一个爪夷文。这些图像采用单色 (黑色、棕红色或深棕色) 或双色 (深棕色、黄棕色或棕红色与黑色) 。描绘的船只可与中国、欧洲和印度尼西亚的本地或远洋船-进行比较。无论是来自本地还是远距离的港口, 这些船-都参与了15-20世纪东南亚海洋贸易和联系。 東北印度洋的船-與海洋活動༚泰國南部Tham Phrayanaga (維京洞穴) 岩石藝術的再分析 Tham Phrayananga是一個在泰國西南安曼海皮皮島上的石灰岩洞穴。2010年的一-調查在三塊不同的畫板上記-了繪在岩壁上的80個圖像。它們包括九種可識別的船只類型、其他無法辨別類型的船舶-非海相圖像和一個爪夷文。這些圖像采用單色 (黑色、棕紅色或深棕色) 或雙色 (深棕色-黃棕色或棕紅色與-色) 。描繪的船只可與中國、歐洲和印度尼西亞的本地或遠洋船-進行比較。無論是來自本地還是遠-離的港口, 這些船-都參與-15-20世紀東南亞海洋貿易和聯系。